Enhancing student engagement and learning outcomes in social studies through Wordwall: A quasi-experimental study in a junior high school context - Wulandari, Fitria Irza; Iskarni, Paus (Universitas Jambi, Indonesia, 2026)
This study investigates the effect of Wordwall, an interactive digital learning medium, on student engagement and learning outcomes in junior high school social studies. Employing a quasi-experimental nonequivalent control group design, the research involved 58 seventh-grade students divided into experimental and control groups. The experimental group received instruction using Wordwall, while the control group followed conventional teacher-centered learning. Data were collected using observation sheets to measure learning activities and achievement tests to assess cognitive outcomes. Descriptive analysis indicated a consistent increase in student engagement in the experimental class across three meetings, with average activity scores rising from 89.52% to 92.56%. Inferential analysis using the Mann–Whitney U test revealed a statistically significant difference in learning outcomes between groups (p < 0.001). The findings suggest that Wordwall effectively promotes active participation and enhances academic achievement, supporting multimedia learning and constructivist perspectives in digital classroom environments.